2013
DOI: 10.1542/hpeds.2012-0041
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Training as a Mechanism for Procedural and Resuscitation Education for Pediatric Residents: A Systematic Review

Abstract: BACKGROUND: Pediatric residents often fi nish their training lacking suffi cient procedural profi ciency and resuscitation experience in the care of critically ill children. Simulation is gaining favor in pediatric residency programs as a modality for procedural and resuscitation education. We reviewed the literature assessing simulation and its role in pediatric resident training. METHODS:We conducted a Medline and PubMed search of simulation training in pediatric resident education from January 2007 to July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 58 publications
0
27
0
3
Order By: Relevance
“…They recommended that future simulation research should include creation of validated assessment tools and applying skills learned to patient care outcomes [35]. The authors of this review performed their own study in 2013, in which high-fidelity simulation was found to enhance pediatric residents' retention, knowledge, procedural proficiency, group resuscitation performance, and experience in pediatric resuscitation compared with matched controls who did not receive simulation training.…”
Section: Principles Of Simulation-based Training For Pediatric Sedationmentioning
confidence: 99%
“…They recommended that future simulation research should include creation of validated assessment tools and applying skills learned to patient care outcomes [35]. The authors of this review performed their own study in 2013, in which high-fidelity simulation was found to enhance pediatric residents' retention, knowledge, procedural proficiency, group resuscitation performance, and experience in pediatric resuscitation compared with matched controls who did not receive simulation training.…”
Section: Principles Of Simulation-based Training For Pediatric Sedationmentioning
confidence: 99%
“…In this era of lesser invasive neonatal practice, it raises a larger question of how trainees can all achieve sufficient experience to be competent. Implementing tools such as simulation or video laryngoscopy may help shorten the learning curve .…”
Section: Discussionmentioning
confidence: 99%
“…Las técnicas de simulación de alta fidelidad permiten recrear el escenario frente a la emergencia con mucho realismo, lo cual facilita el aprendizaje, complementado con el "debriefing", que genera un alto grado de retención del conocimiento incorporado. 15,16 En un estudio realizado por Mills y col., se comparó el desempeño al año de capacitación en reanimación pediátrica con un grupo control histórico y, si bien observaron escasa diferencia en general, se produjo un aumento en las intubaciones realizadas por los residentes, de manera secundaria a un aumento en la autoconfianza. 17 En otro estudio recientemente publicado, Sidhu y col. evaluaron en forma retrospectiva el desempeño en el manejo clínico de los casos de anafilaxia en un hospital pediátrico de los EE.…”
Section: Discussionunclassified